Biomechanics, Mechanisms, Prevention and Characteristics of Knee Injuries in Recreational and Sports Alpine Skiing: A Narrative Review - Szczęsny, Mikołaj; Katra, Małgorzata; Ślot, Marcin; Pal, Adrian; Cienkowski, Krzysztof; Cegiełka , Patryk; Żeżawska , Karolina; Głowacka , Izabella; Adamczyk, Aleksandra; Sicińska, Maria (Quality in Sport, 2026)
Background Alpine skiing is a popular winter sport but is associated with a considerable risk of musculoskeletal injuries. Among them, knee injuries are the most frequent and clinically significant, particularly ruptures of the anterior cruciate ligament (ACL). The combination of high skiing speed, rotational forces, and interaction with modern ski equipment contributes to complex mechanisms leading to knee joint trauma in both recreational and competitive skiers. Aim The aim of this study was to review current knowledge on the biomechanics, mechanisms, characteristics, and prevention of knee injuries in alpine skiing. Material and methods A literature review was conducted using the following databases: PubMed, Scopus, and Web of Science. The review included publications published between 2000 and 2025. The following keywords and their combinations were used with Boolean operators: “alpine skiing”, “knee injury”, “ACL injury”, “anterior cruciate ligament”, “MCL injury”, “meniscus injury”, “ski injury epidemiology”, “injury mechanism”, “return to sport”, and “injury prevention in skiing”.. Results The knee joint accounts for approximately one-third of all alpine skiing injuries, with ACL rupture being the most common severe injury. Most cases occur through non-contact mechanisms such as slip-catch, phantom foot, dynamic snowplow, and landing back-weighted. These mechanisms involve valgus loading, tibial rotation, and anterior tibial translation. Major risk factors include high speed, fatigue, neuromuscular deficits, equipment characteristics, and environmental conditions. Conclusions Knee injuries in alpine skiing result from complex interactions between biomechanical forces, skiing technique, and equipment. Understanding these mechanisms is essential for prevention. Targeted neuromuscular training, skier education, and proper equipment adjustment may help reduce injury incidence and improve safety.